2017
DOI: 10.1302/1863-2548-11-160175
|View full text |Cite
|
Sign up to set email alerts
|

Is percutaneous medial hamstring myofascial lengthening as anatomically effective and safe as the open procedure?

Abstract: BackgroundMedial hamstring fractional lengthening is commonly performed in children with cerebral palsy (CP) to decrease contracture and/or to improve gait. Percutaneous procedures are gaining more and more popularity, even in the paediatric population, with equivocal results. The purpose of this paper was to determine the efficacy and safety of percutaneous medial hamstring myofascial lengthening (PHL).MethodsThis is a prospective randomised controlled trial including 31 knees from 18 consecutive patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 24 publications
1
13
0
4
Order By: Relevance
“…In this study, we did not evaluate the postoperative recurvatum deformity in patients but all of them had isolated hamstring contracture and no one had gastrocnemius spasticity. In a recent study by Mansour et al 11 , although unacceptable damage to the muscular portion of both medial hamstrings with percutaneous lengthening occurred, they did not encounter any correlation between the PA gain and development of recurvatum deformity This study has some limitations like other retrospective studies with this group of patients. The patient population is small, postoperative followup is lacking and the patients were not evaluated according to the necessity of biceps tenotomy.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…In this study, we did not evaluate the postoperative recurvatum deformity in patients but all of them had isolated hamstring contracture and no one had gastrocnemius spasticity. In a recent study by Mansour et al 11 , although unacceptable damage to the muscular portion of both medial hamstrings with percutaneous lengthening occurred, they did not encounter any correlation between the PA gain and development of recurvatum deformity This study has some limitations like other retrospective studies with this group of patients. The patient population is small, postoperative followup is lacking and the patients were not evaluated according to the necessity of biceps tenotomy.…”
Section: Discussionmentioning
confidence: 67%
“…In a recent prospective anatomical study showing the effectiveness and safety of PHL, undesirable extensive muscle injury was reported with this percutaneous technique 11 . Although any accidental injury to the surrounding structures and neurovascular complications with PHL surgery was reported, they did not recommend PHL instead of OHL because of the unexpected muscle injury and less gain in PA with PHL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have demonstrated that those who had additional orthopaedic surgery were more flexed during gait before surgery and therefore had more improvements post-operatively. However, long-term results may be influenced by the type of orthopaedic surgery performed in the different surgical centres and one centre routinely carries out percutaneous hamstring lengthening’s potentially leading to increased injury to the muscle versus open lengthening [22].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have noted that without active physiotherapy and orthopaedic interventions children with CP can worsen physically, falling in a lower Gross Motor Function Classification System (GMFCS) level (Novak, 2014). (Mansour et al, 2017;Mitsiokapa et al, 2010).…”
Section: Introductionmentioning
confidence: 99%